Application of membrane separation in biotechnology - Ismail, Ahmad Fauzi; Lai, Ping Yean (2001)
Membrane technology emerges as one of the most important separation methods, which have captured the attention of industries, related to biochemical, pharmaceutical, biomedical, and food industries. Due to the current intensive development and expansion, membrane technology is also rapidly gaining market recognition and application in Malaysia. Factors accelerating the positive growth of membrane market in Malaysia include economic factors, technology, support industries and awareness in environmental safety and health. Therefore, this paper seeks to review the separation mechanism, advantages and applications of synthetic polymeric membranes in biotechnology.